Potential of ultrasound treatment for sludge reduction - Minervini, Davide (Cranfield University, 2008)
The potential of ultrasound treatment for sludge reduction during the activated sludge process was assessed. Batch and dynamic disintegration studies were completed using an activated sludge pilot-scale plant fed with settled sewage that was comprised of two 1.2 m3 lanes, operated as a test and control. A 1 kW ultrasound system was integrated into the test lane of the pilot-scale plant to allow continuous in-line ultrasound treatment of the return activated sludge (RAS). Seven dynamic trials were completed over an 8-month period, treating from 1.7 to 12.5% of the RAS with energy densities between 42 and 168 kJ L-1. During the batch disintegration studies, it was observed that ultrasound treatment at 42 to 186 kJ L-1 caused floc breakage and sludge solubilisation. Floc size was reduced by 88% at 42 kJ L-1 while the degree of soluble COD release increased almost linearly from 11 to 36 % between 42 to 168 kJ L-1. A change in the biological activity was observed only at 168 kJ L-1 with an 8.5 % increase in the specific oxygen consumption of the treated RAS samples in comparison to the untreated ones. During the dynamic studies, a 20% degree of sludge reduction was observed treating 10% of the RAS at 42 kJ L-1. At these operational conditions, there was no significant difference in the total COD and nitrogen removal between the control and test lanes. However, a 5.5-fold increase in the capillary suction time and a 3.6-fold increase in the specific resistance to filtration in the RAS from the test lane indicated a detrimental impact on dewaterability. Increasing the energy input, by treating 12.5% of the RAS at 84 kJ L-1, did not result in a significant increase in sludge reduction, which indicates that there might be limits to the degree of reduction achievable with the ultrasound treatment. Results from the dynamic studies suggested that lysis-cryptic growth was the main mechanism behind the observed sludge reduction. Based on modelling, lysis-cryptic growth could justify 98 % of the sludge reduction observed. Cost analysis results indicated that sludge reduction by ultrasound disintegration was not currently economically viable unless the cost for sludge treatment and reuse increased to £ 961 from the reference price of £ 423 per tonne of dry solids.